Three-Dimensional Correction of Hallux Valgus Deformity: A Novel Technique. Issue 1 (March 2022) - Zein, Abo Bakr; Elhalawany, Ahmed S.; Nagy, Mohamed; Kholeif, Ahmed; El Barbary, Hassan; Hegazy, Mohamed; Afifi, Ahmed
Abstract : Background: Minimally invasive techniques for forefoot surgery are increasingly used nowadays with short operative time and smaller incisions allowing early rehabilitation. Consequently, the purpose of this study was to evaluate a novel technique for 3-dimensional correction of hallux valgus deformity using small incisions. Materials and methods: A single-center, prospective study was conducted from February 2016 to February 2019. The study included a total of 36 feet in 34 patients with hallux valgus deformity treated with soft tissue release combined with osteotomy of the first metatarsal base with correction of angular, rotational deformities of the hallux and fixation by transverse pinning to the second metatarsal. Patients were assessed radiographically for union and measurements as well as clinically using the "The American Orthopedic Foot and Ankle Society (AOFAS)" for functional assessment. Results: Union was achieved in all cases. Hallux valgus angle improved from a mean of 40±5.9 degrees to a mean of 9.1±2.3 degrees ( P <0.001). Intermetatarsal angle improved from a mean of 17.5±2.1 degrees to a mean of 6.1±1.5 degrees ( P <0.001). At the final follow-up period (2 y), the mean hallux valgus angle was 10.9±2.8 degrees ( P <0.001) and the mean intermetatarsal angle was 7±1.7 degrees ( P <0.001). Conclusion: This technique yielded good radiographic and functional outcomes and can be a viable option in management of mild, moderate, and severe cases of hallux valgus deformity. Level of Evidence: Level IV, Therapeutic study.